Oral Presentation No. 84 Initial clinical experience with 6-hour enoxaparin regimen in opiate-treated patients undergoing primary percutaneous coronary intervention. (21st October 2022) - Elamin, Nadir; Ow, Kok Weng; Parker, William A E; Nelson, Thomas A; Middle, Janet; Hanson, Jessica; Moyle, Bethany; Krishnamurthy, Arvindra; Barmby, David; Morgan, Kenneth; Adam, Zulfiquar; Rothman, Alexander; et al.
Abstract: Background: Opioid treatment delays the onset of oral P2Y12 inhibitors in patients with acute ST-segment elevation myocardial infarction (STEMI), leading to suboptimal antithrombotic therapy during primary percutaneous coronary intervention (PPCI). Material and methods: We retrospectively compared using a prolonged enoxaparin regimen (0.75 mg/kg bolus followed by 6-hour intravenous infusion) to using unfractionated heparin (UFH) with or without tirofiban in opioid-treated patients with STEMI who underwent PPCI. We compared the proportions of acute stent thrombosis (AST) and bleeding events according to the bleeding academic research consortium (BARC) within 24 hours post-PPCI. Results: 270 opioid-treated patients with a mean age of 63 [SD ± 12] years were enrolled, of which 49 (18%) were with diabetes mellitus (DM). 90 (34%) patients (mean age 61 [SD ± 11] years) received enoxaparin, 110 (41%) (mean age 65 [SD ± 14] years) UFH with tirofiban, and 69 (25%) (mean age 63 [SD ± 12] years) UFH only. Compared to the other strategies, a higher proportion of DM was observed in the enoxaparin-treated group (21%). No AST was associated with enoxaparin compared to 2 (1.8%) events in UFH with tirofiban and 1 (1.4%) in UFH only. The rate of severe bleeding events (BARC 2 and 3) was significantly lower in the enoxaparin-treated patients than in UFH with tirofiban (0 (0%) vs. 8 (7%), P = 0.01). 3 enoxaparin-treated patients needed switching to tirofiban as a bailout strategy due to distal vessel embolisation. Conclusions: The novel 6-hour enoxaparin regimen is safe during PPCI and was associated with fewer bleeding events than UFH with tirofiban.